Systematic review and consensus definitions for the Standardised Endpoints in Perioperative Medicine (StEP) initiative: patient comfort. (April 2018) - Myles, P.S.; Boney, O.; Botti, M.; Cyna, A.M.; Gan, T.J.; Jensen, M.P.; Kehlet, H.; Kurz, A.; De Oliveira, G.S.; Peyton, P.; Sessler, D.I.; Tramèr, M.R.; et al.
Abstract: Background: Maximising patient comfort during and after surgery is a primary concern of anaesthetists and other perioperative clinicians, but objective measures of what constitutes patient comfort in the perioperative period remain poorly defined. The Standardised Endpoints in Perioperative Medicine initiative was established to derive a set of standardised endpoints for use in perioperative clinical trials. Methods: We undertook a systematic review to identify measures of patient comfort used in the anaesthetic, surgical, and other perioperative literature. A multi-round Delphi consensus process that included up to 89 clinician researchers was then used to refine a recommended list of outcome measures. Results: We identified 122 studies in a literature search, which were the basis for a preliminary list of 24 outcome measures and their definitions. The response rates for Delphi Rounds 1, 2, and 3 were 100% ( n =22), 90% ( n =79), and 100% ( n =13), respectively. A final list of six defined endpoints was identified: pain intensity (at rest and during movement) at 24 h postoperatively, nausea and vomiting (0–6 h, 6–24 h, and overall), one of two quality-of-recovery (QoR) scales (QoR score or QoR-15), time to gastrointestinal recovery, time to mobilisation, and sleep quality. Conclusions: As standardised outcomes will support benchmarking and pooling (meta-analysis) of trials, one or more of these recommended endpoints should be considered for inclusion in clinical trials assessing patient comfort and pain after surgery.